Composition of Togok Catch in Kuala Tungkal, Tanjung Jabung Barat, Jambi - Muhammad Mauliddin; Nofrizal Nofrizal; Romie Jhonnerie (Jurnal Perikanan dan Kelautan, 2022)
Togok is one of the fishing gear that is operated in Kuala Tungkal, Tanjung Jabung Barat Regency, this fishing gear is in the form of a conical net body whose arms are tied to two poles and the success of catching it relies on currents, togok fishing gear is used by Kuala Tungkal fishermen to catch rebon shrimp (Acetes japonicas) but in operation, there are many other types of catch. This study aims to determine the main catch, bycatch, and discards, and to determine the size as well as the number of togok catches. This research was conducted on April 5 – July 10, 2021. This research was conducted using experimental fishing methods, namely by conducting direct operations with local fishermen. The results of the study that the percentage of the catch of main catch by 28%, bycatch 51%, and discard 21%. For the size of the catch of togok species of shrimp (crustacean), there are many sizes that have reached maturity or are suitable for catching while in the catch of fish species there are many sizes that are not yet mature. And for the number of catches in the catch togok main catch amounted to 550800 tail, the catch of the bycatch 79281 fish, and the catch of the discard 10186 fish